ANALISIS PRIORITAS SOLUSI KEMACETAN LALU LINTAS DI KOTA DENPASAR DENGAN MENGGUNAKAN METODE ANALYTIC NETWORK PROCESS - ISMIRANTI, NI WAYAN NINING; KENCANA, I PUTU EKA N.; SUKARSA, I KOMANG GDE (E-Jurnal Matematika; Vol 5 No 1 (2016), 2016)
The aim of this research is to find the alternative solutions that could be used to handle the traffic congestions in the Denpasar City and the priorities of each alternative. The  main problem of this research is determining the appropriateness of alternatives and its criterias that could be used to set the priorities of the alternatives. Based on the interview with the  transport experts of Denpasar City, there are three main factors that affect the traffic congestion i.e (1) the ratio of the volume of vehicles on the road capacity, (2) the existing traffic management, and the traffic regulation . The  interviewee also suggest that there are six alternatives that can be used to handle traffic congestion. These alternatives are (1)improve the public transport system, (2) use technology to monitor and enforce the rules,(3) create a  3 in 1 rule, (4) create  road pricing rule,(5) optimize the  existing management  in the road, and (6) create rule of road zoning. Based on the calculations by Analytic Network Process (ANP) method, improving the public transport system is the best alternative among others that is appropriate to handle traffic congestion in the Denpasar City.
Keywords: Analytic Network Process; Traffic Congestion; Priorities; Denpasar